Looking for meaningful disruptive innovation: counterattack from Pinduoduo. Issue 1 (2nd January 2022) - Chen, Honghua; Zang, Shuwei; Chen, Jin; He, Wentian; Chieh, Hang Chang
ABSTRACT: The disruptive innovation theory has been regarded as a theoretical basis for latecomer firms to enter the market and achieve latecomer transcendence. With the help of typical cases, this paper discusses the issues related to the disruptive innovation of latecomer firms from the perspective of timing selection and business model innovation, and combines the concept of meaningful innovation to provide relevant enlightenment. The study has found that the proper market entry timing is the precondition for latecomer firms to successfully open up non-mainstream segment market, and the business model innovation determines whether the latecomer firms can lead in the non-mainstream market and successfully turn to the mainstream market. The combination of market entry timing selection and business model innovation is an essential way for latecomer firms to take on leading firms through disruptive innovation. These findings enrich and expand the connotation dimensions of the disruptive innovation theory, and provide theoretical guidance for the latecomer firms in developing countries to identify innovation opportunities, open up a new blue ocean market and successfully catch up.